The Hidden Costs of Hidden Debt - Johan Almenberg; Artashes Karapetyan (Norges Bank, 2011)
We report evidence that salience may have economically significant effects on homeowners' borrowing behavior, through a bias in favour of less salient but more costly loans. Survey evidence corroborates the existence of such a bias. We outline a simple model in which some consumers are biased and show that under plausible assumptions this affects prices in equilibrium. Market data support the predictions of the model.
hdl:11250/2496937
Keywords: D12; G14; G21; G32; 330; salience; debt; housing market; co-op; capital structure